Creating Nature-Friendly Behaviour in Nursery School Student - Rangkuti, Zulkifli; Sastradiharja, EE. Junaedi; Al Wahid, M. Azhar; Bahagia, Bahagia; Wibowo, Rimun (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the activities in learning to foster friendly behavior towards nature for children at the kindergarten level. The research method used a descriptive qualitative approach. In-depth interviews were used to collect data. The sample was selected through a purposive technique. The results are probed through triangulation techniques and triangulation sources. The research results show that a school that combines nature and school, even though it is not natural, plays a crucial role in fostering environmentally friendly behavior in children. The comprehensive environment provided by the school significantly influences children's behavior, as it meets their needs and encourages them to care for nature. However, it's important to note that there are children who like closed spaces. In addition, educational tours are a way to educate children and get to know the world of animals and plants firsthand. These stimuli can make children behave in caring for nature. Then, children given a garden visit learning method can let the child know the natural environment around them, starting from how to produce crops, harvest, and process crops—coupled with science learning where the events in the environment are used as an experiment in class. The impact is to make children know the causes and effects of events; it stimulates children to think creatively, analyze events, and become critical because they immediately see events. Friendly classrooms also include support for making children behave in a nature-friendly manner, and learning how to process waste from an early age makes it a habit not to produce much waste.